Dynamics of family fiqh: the multiple roles of women in realizing family resilience - Tri Wahyu Hidayati; Ulfah Susilawati; Endang Sriani (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2022)
This research seeks to reveal the multiple roles of working women in realizing family resilience. This research argues that family resilience will determine the resilience of a nation. The research was conducted through interviews and observations on 15 civil servants (PNS) at the State Islamic University (UIN) of Salatiga. They consisted of 6 lecturers, 6 educational staff, and 3 postgraduate students. The results of the study show that women had a central role in realizing family resilience. The multiple roles that women played as a wife, mother, community member, and worker indicate their strong personality. They were women who were able to pursue their family resilience in their own way, depending on the conditions and situations that they faced. They were not only concerned with domestic affairs, but also other affairs in society and at work. They were able to negotiate their multiple roles to maintain their existence without abandoning their role in the family as a wife and mother. Some of the important practices that these women implemented include building communication and openness, implementing the principle of mutuality in carrying out tasks at home, acting smart to seize opportunities and not being monotonous, setting priorities between several tasks or jobs, and increasing spirituality/religiosity and minimizing negative effects of using social media on children.